2019
DOI: 10.1177/0363546519880528
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Magnetic Resonance Imaging for Detecting Meniscal Ramp Lesions in Patients With Anterior Cruciate Ligament Tears: A Systematic Review and Meta-analysis

Abstract: Background: The clinical importance of meniscal ramp lesions in patients with anterior cruciate ligament (ACL) tear has emerged as a major issue. However, the diagnostic accuracy of magnetic resonance imaging (MRI) for detecting ramp lesions has a wide range. Purpose: To perform a systematic review and meta-analysis of the diagnostic performance of MRI for diagnosing ramp lesion in patients with ACL tear. Study Design: Systematic review and meta-analysis. Methods: A literature search of PubMed, EMBASE, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 35 publications
2
43
1
Order By: Relevance
“…Diagnosing ramp lesions by imaging is exceedingly difficult, with an average MRI sensitivity of 71% according to a recent meta-analysis. 6 Malatray et al 9 reported a sensitivity of only 23.2% using MRI in their pediatric study. Meniscal vascularization in children can generate false-positive cases.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Diagnosing ramp lesions by imaging is exceedingly difficult, with an average MRI sensitivity of 71% according to a recent meta-analysis. 6 Malatray et al 9 reported a sensitivity of only 23.2% using MRI in their pediatric study. Meniscal vascularization in children can generate false-positive cases.…”
Section: Discussionmentioning
confidence: 95%
“…MRI sensitivity may well have been improved with 3-T instead of 1.5-T magnet machines. 6 Finally, there was a variable interval between the preoperative MRI and the surgery, allowing for either further meniscal tears or spontaneous healing in this time frame, depending on the case.…”
Section: Discussionmentioning
confidence: 99%
“…However, the predicted diagnostic values by the logistic regression equation were an AUC of 0.779, a sensitivity to detect ramp lesions of 75.8%, and a specificity of 71.7%, which were comparable with MRI values, although MRI values were somewhat higher. 2,21,23 The diagnostic values were calculated regardless of the direct positive findings of ramp lesions on MRI. Thus, MRI evaluation would be considered a first-line diagnostic tool, but these risk factors could also be used as a supplementary diagnostic tool to suspect ramp lesions in ACL-injured knees irrespective of the direct findings with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…23,29,31,37 They are sometimes referred to as “hidden lesions” 31 because, on one hand, their posterior location behind the medial tibiofemoral joint often makes them hard to see on the standard anterior arthroscopic view 31 (hidden by the medial femoral condyle) and, on the other, they are very hard to identify using preoperative magnetic resonance imaging because of the low sensitivity of this modality. 3,7,11,17…”
mentioning
confidence: 99%